BREASTFEEDING PRACTICES [POSITIONING, ATTACHMENT/LATCHON AND EFFECTIVE SUCKLING]: STUDI FROM MATERNAL AGE, PARITY, EDUCATION, MATERNAL OCCUPATION, BREAST DISEASES, GESTATION AND BIRTH WEIGHT IN SIDOARJO GENERAL HOSPITAL - Rinata, Evi; Sari, Putri Anjar (Asosiasi Pendidikan Kebidanan Indonesia, 2017)
The scope of the exclusive breastfeeding in Indonesia based on basic health research (Riskesdas) in 2013 reached 30,2%, still far from target nationally by 80%. Based on research conducted in developing countries showed that infants were not breastfed would have a risk 6â10 times higher died in the first few months of life. This will impact the Infant Mortality Rate (IMR). The purpose of this research is to know the relation motherâs age, parity, education, maternal occupation, breast diseases, gestation and birth weight to breastfeeding practices. This research usesÂ analytic cross sectional design with the entire population of parturition and the maternal mother who came to breastfeeding her infant at Sidoarjo General HospitalÂ in 14-27 July 2015. Using primary data with interviews and observations and also secondary data. Using the samplingÂ probability sampling, simple random sampling technique. The number of samples as much as 45 nursing mothers from 51 populations. The results of the test statistic chi-square showed no relationship to maternal age with position (p=0.929) and bonding (p=0.569). There is no relationship to parity with position (p=0.122), but found a significant relationship between bonding with parity (P=0.024). Education is not associated with the position(p=0.806) and bonding (p=0.595). No relation to maternal occupation with position (p=0.395) and bonding (p=0.329). Breast disease significantly shows there is a relationship with position (p=0.009) and bonding (p=0.000). Gestational there is no relationship with bonding (p=0.767) and effectiveness of contact (p=0.500). There is no relationship of weight born by bonding (p=0.754) and effectiveness of contact (p=0.519). The conclusion of the research that is no relationship between maternal age, education, maternal occupation, gestation and birth weight with breastfeeding practices. There is a relationship between parity and breast diseases with breastfeeding practices. Â Keyword : Attachment, breastfeeding practices, effective suckling, positioning